Approximation relations on the posets of pseudometrics and of pseudoultrametrics - Nykorovych, S.I. (Carpathian Mathematical Publications, 2016)
We show that non-trivial "way below" and "way above" relations on the posets of all pseudometrics and of all pseudoultrametrics on a fixed set X are possible if and only if the set X is finite.